A Review of Circularity Indicators and Psychological Factors: a Comprehensive Analysis of Circularity Practices in Organizations - Birgovan, Andreea Loredana; Lakatos, Elena Simina; Nita, Viorel; Sim, Anamaria (Dr. Viktor Koval, 2024)
Introduction. In a booming global economy of finite resources, pandemics, armed conflict and irresponsible over-consumption, attention to the nature of finite resources becomes imperative. The transition to a circular economic model lies at the intersection of economic development and environmental protection needs, significantly impacting today's society and future generations. Research and understanding of the circular economy are catalysts for accelerating processes to change the current unsustainable paradigm. This study reviews the literature and identifies how circularity indicators are addressed at the organisational level. Aim and tasks. The study aims to review and synthesise the literature on micro-level circular indicators, psychological factors, and relevant theories in the context of organisational performance, as well as identify knowledge gaps and ways the two elements can be integrated into the circularity assessment. Results. The study shows no universally accepted method to measure the circular economy at the organisational level. Most indicators focus only on the environment, ignoring the social dimension, while many indicators in the literature are not standardized and cannot be compared. It has also been identified that the social component needs to be better represented, with all the attention focused on the environment. Within the social component, organisational psychology (organisational culture, satisfaction, attitudes, leadership, motivation, and employee well-being) is almost not represented in the studies and indicators, as they are highly relevant to the social component. Conclusions. This systematic review provides an overview of existing indicators and measurement tools at the organisational level. Following the analysis and results presented above, it can be said that although underexplored, the social dimension of the circular economy has begun to attract attention in the literature. The present research highlights the relevance of the social aspect in the circular economy and suggests that it has been undervalued in research to date. Irrespective of the specific areas of interest of different studies, there is a growing need for a more comprehensive understanding of the social impact of the circular economy, which would include all aspects of social life, from jobs and education to civic engagement and behaviour change.